NILAI PENDIDIKAN KARAKTER DALAM NOVEL ANAK RANTAU KARYA AHMAD FUADI - Savitri, Veronika One; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem of this research was the analysis of the value of character education in the novel Anak Rantau by Ahmad Fuadi. Novel Anak Rantau tells the story of a child named Hepi who was abandoned by his father in Tanjung Durian village and lived with his grandparents. The problems of this research are: (1) the value of honest character education, (2) the value of hard work character education, (3) the value of sincere character education. The purpose of this research is to describe the value of character education and reader responses. This study uses a description method with qualitative research forms. Data from this study are sentences that show the value of honest character education, hard work, and sincerity. The technique used in this study is documentary study, and the data collection tool is the researcher himself as a key instrument. Based on the results of data analysis there are 36 data values of honest character education, 22 data on the value of character hard work education, and 35 data on the value of sincere character education.Keywords: Value of Character Education, Anak Rantau